Accountability Myopia: Losing Sight of Organizational Learning - Ebrahim, Alnoor (Nonprofit and Voluntary Sector Quarterly, 2005)
This article challenges a normative assumption about accountability in organizations: that more accountability is necessarily better. More s pecifically, it examines two forms of “myopia” that characterize conce ptions of accountability among service-oriented nonprofit organization s: (a) accountability as a set of unconnected binary relationships rat her than as a system of relations and (b) accountability as short-term and rule-following behavior rather than as a means to longer-term soc ial change. The article explores the effects of these myopias on a cen tral mechanism of accountability in organizations—evaluation—and propo ses a broader view of accountability that includes organizational lear ning. Future directions for research and practice are elaborated.
Keywords: IMPORTANT